Handbook of the Sociology of Gender - Chafetz, Janet Saltzman (Springer, 2006)
During the past three decades, feminist scholars have successfully demonstrated the ubiquity and omnirelevance of gender as a sociocultural construction in virtually all human collectivities, past and present. Intrapsychic, interactional, and collective social processes are gendered, as are micro, meso, and macro social structures. Gender shapes, and is shaped, in all arenas of social life, from the most mundane practices of everyday life to those of the most powerful corporate actors. Contemporary understandings of gender emanate from a large community of primarily feminist scholars that spans the gamut of learned disciplines and also includes non-academic activist thinkers. However, while incorporating some cross-disciplinary material, this volume focuses specifically on sociological theories and research concerning gender, which are discussed across the full array of social processes, structures, and institutions. As editor, I have explicitly tried to shape the contributions to this volume along several lines that reflect my long-standing views about sociology in general, and gender sociology in particular. First, I asked authors to include cross-national and historical material as much as possible. This request reflects my belief that understanding and evaluating the here-and-now and working realistically for a better future can only be accomplished from a comparative perspective. Too often, American sociology has been both tempero- and ethnocentric. Second, I have asked authors to be sensitive to within-gender differences along class, racial/ethnic, sexual preference, and age cohort lines. This request reflects the growing sensitivity of feminist scholars to the white, middleclass, and heterosexist biases implicit in much of our past work, which has effectively glossed over differences among women (especially) and consigned many categories of women to invisibility. Third, I have intentionally omitted a chapter on men and masculinity and asked authors to take seriously the fact that there are two genders that require examination and comparison. Too often, works in gender sociology are about women only or, less frequently, men only. Just as one cannot understand the experiences, constraints, and consciousness of an ethnic or racial minority without understanding its relationship to the dominant group, one cannot understand those of women apart from their relationship to men, culturally defined masculinity and male-dominated institutions. Indeed, one cannot adequately understand dominant groups without simultaneously examining their relationships to subordinate groups. Happily, the chapter authors have taken my various suggestions seriously, to the extent that available research and space in this volume permit.